PENINGKATAN HASIL BELAJAR BIOLOGI SISWA SMAN 1 PEKANBARU DENGAN MENERAPKAN MODEL PEMBELAJARAN COOPERATIF LEARNING TYPE STAD - Wan Roswita (Jurnal Pendidikan, 2013)
Student is interest in learning hasn’t reached the National Education Standard goal andpurposes. Students intended to be passive and less creative in way to find their own concept of easylearning and towards the concept of studying it self. The research model of cooperative learning typeSTAD has been done for 2 cycles with 5 time meetings in class X.3. In every meeting study groupapplied then each group presented their material one by one to be proceed to quizzes. One cyclesclosed with daily review. Before treatment only 14 student out of 31 student in class X.3 who areeligible in KKM standard. After cooperative learning method type STAD has applied the students whofulfilled the KKM standard rose into 20 student during first cycle and added into 22 student for cycle 2.This model of learning has contributed to the increasing of the score even though percentage does not yet climb to 85% (45,16% before treatment, 64,52% first cycle, 70,97% second cycle). Roughlyscore for UH 1 (7,33), UH2 (7,99). The average students score for cycle one is 7,20 and 8,07 forcycle two. Student has not yet in a state of brave to communicate their minds meanwhile the rest ofcategories are fine yet excellent.Key Words : Applied Cooperative Learning, Biology, and Result of Study